Climate effects of carbon taxes, taking into account possible other future climate measures - Florian Habermacher; Gebhard Kirchgässner (Center for Economic Studies and ifo Institute (CESifo), 2011)
The increase of fuel extraction costs as well as of temperature will make it likely that in the medium-term future technological or political measures against global warming may be implemented. In assessments of a current climate policy the possibility of medium-term future developments like backstop technologies is largely neglected but can crucially affect its impact. Given such a future measure, a currently introduced carbon tax may more generally mitigate climate change than recent reflections along the line of the Green Paradox would suggest. Notably, the weak and the strong version of the Green Paradox, related to current and longer-term emissions, may not materialize. Moreover, the tax may allow the demanding countries to extract part of the resource rent, further increasing its desirability.
Keywords: Q54; Q31; Q38; Q41; Q42; 330; climate change policy; greenhouse gas tax; carbon tax; Green Paradox; anticipation effects; exhaustible resources; fossil fuels market; backstop technology; uncertainty; resource rent; Ökosteuer; Steuerwirkung; Klimaschutz; Ankündigungseffekt; Erschöpfbare Ressourcen; Ressourcenökonomik; Ökonomischer Anreiz; Luftreinhaltung; Klimaveränderung; Theorie